2019
DOI: 10.15406/ppij.2019.07.00239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hypertension related knowledge, attitudes and practices at community level in Kabul 

Abstract: Background: Evaluation of knowledge, attitudes, and practices plays key role in hypertension control. Since little data is available from Kabul, Afghanistan, hence this study was planned to generate scientific data about it. Methods:A cross-sectional, descriptive, questionnaire based survey was designed to cover the study participants from general public of Kabul City. A 30 item pretested questionnaire was served to collect the data.Results: A total of 201 out of 384 adult individuals of either gender voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…People will misinterpret the disease and will go undiagnosed [28]. This lack of knowledge regarding HTN's symptoms could affect healthcare-seeking behavior [31]. Community awareness campaigns could enhance the public's knowledge of HTN's symptoms and promote the screening and diagnosis of HTN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People will misinterpret the disease and will go undiagnosed [28]. This lack of knowledge regarding HTN's symptoms could affect healthcare-seeking behavior [31]. Community awareness campaigns could enhance the public's knowledge of HTN's symptoms and promote the screening and diagnosis of HTN.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies reported high knowledge of HTN-related complications among their participants [16,24,32]. This lack of knowledge regarding complications could affect the perception of HTN threat as a silent killer [31] and the adoption of healthy lifestyle modification to prevent the complications [7,8,33]. It is worth paying attention to the people with inadequate knowledge since it could be a factor of complications and subsequent disability [16].…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al informed that the knowledge and belief of hypertension prevention were good in Shanghai [8]. Bashaar et al stated that the hypertension related knowledge among respondents was found to be good at community level in Kabul [9]. Sabouhi et al informed that among the hypertensive patients referring to public health care centers in Khoor and Biabanak, patients relatively had high awareness, knowledge about hypertension [2].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the participants pointed out stigma from relatives and community at large as another major challenge mainly due to limited knowledge of the conditions in the society. This shows need for community education on NCDs for the families and the public as highlighted in the key literature reviewed 6,8,9,14 .…”
Section: Discussionmentioning
confidence: 95%
“…A literature scan reveals a dearth in studies focusing on knowledge, attitudes and perceptions on NCDs in LMICs and the SSA region. Most of the studies focusing on the knowledge, attitudes, and practices on NCDs were conducted in India 8 , 9 and Pakistan 10 . To our knowledge studies conducted in the SSA region do not assess patients' knowledge and perceptions regarding the comorbidity of HIV and NCDs.…”
Section: Introductionmentioning
confidence: 99%